Relationship between reaction time and anaerobic power in different sports - Almuzaini, K. S.; Al-Hazzaa, H. M.; Alablood, S. A.; Sulaiman, M. A.; Dafterdar, M. Y. (Medicine & Science in Sports & Exercise, 1998)
Anaerobic power and whole-body reaction-movement time were measured among athletes aged 18-26 years: long-distance runners (N = 13), sprinters (N = 12), fencers (N = 13), table tennis players (N = 12), and a control group (N = 8). All groups performed a vertical jump, a Wingate power test, and reaction time tests using light, sound, and choice of lights.